The Effect of Implementing Formative Assessment with the 5E Learning Cycle Model on High School Students' Scientific Reasoning Abilities - Alfira Eka Putri; Ana Ratna Wulan (Journal of Educational Sciences, 2026)
Students’ scientific reasoning abilities remain relatively low, often due to limited interactive learning and insufficient feedback during instruction. This study investigates the effect of implementing formative assessment within the 5E Learning Cycle model to enhance these abilities. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The sample consisted of 35 eleventh-grade students from a public high school in Bandung, selected through purposive sampling. Research instruments included a scientific reasoning ability test and formative assessment sheets. The findings reveal a significant improvement in students’ scientific reasoning after the intervention. Results from the paired sample t-test indicate a statistically significant difference between pretest and posttest scores (p < 0.05), with an effect size of 4.64, categorized as very large. Additionally, students’ average formative assessment scores increased from 67.42 in the first meeting to 80.12 in the second meeting. These results suggest that integrating formative assessment into the 5E Learning Cycle model provides meaningful feedback and promotes active engagement, leading to substantial improvements in scientific reasoning. Therefore, this approach can be considered an effective strategy to support higher-order thinking skills in science learning.